Reconstruction with a cage outlives patients with metastatic disease involving the acetabulum. Issue 3 (May 2023) - Shiels, Sarah J; Gosling, Oliver; Mehendale, Sanchit A; Baker, Richard P
Aim: The aim of this study was to determine whether patients treated with a caged reconstruction for metastatic acetabular disease would have a construct survival superior to that of their life expectancy. Patients and methods: We undertook a retrospective study, in a single centre in the United Kingdom, reviewing outcomes for 19 patients (20 hips) treated with a cage reconstruction for metastatic disease of their acetabulum over 6 years. Inclusion criteria were those with an impending fracture of the acetabulum, metastatic dissociation, fracture of the acetabulum and or femur and those whose life expectancy was considered by the oncology team to be >6 months. Results: In all patients the Restoration GAP II acetabular cage (Stryker, Howmedica Osteonics Corp, NJ, USA) was used in conjunction with a cemented acetabular cup and cemented femoral stem. The mean age at the time of surgery was 68 (44–87) years with breast cancer being the most common primary malignancy (31%) followed by prostate cancer (26%). Radiological survivorship estimates were 94.1% (95% CI, 99.2–65.0) at 12 and 24 months, 70.6% (95% CI, 93.6–16.0) at 36 months and 35.3% (95% CI, 78.2–1.2) at 48 months. There were 3 radiological failures of the implant due to disease progression. Complications occurred in 3 patients with 2 developing deep infection which was treated with suppressive antibiotic therapy following aspiration of the hip. 1 patient suffered a hip dislocation following trauma which was successfully reduced closed and no further intervention was required. Conclusions: This study represents the first published case series of the use of the GAP II cage in patients with metastatic acetabular disease. The construct generally outlives the patient and hence is suitable for the treatment of acetabular metastases.